Implementasi Support Vector Machine (SVM) Untuk Deteksi Serangan Jaringan Pada Sistem Keamanan Jaringan Kampus - Darip, Mochammad; Sapaatullah, Asep; Rahmat, Rahmat (Bulletin of Information Technology (BIT), 2026)
Network security in campus environments faces increasingly complex challenges due to the rapid growth of internet usage, digital academic systems, and the large number of devices connected to the network. One of the main problems is the limitation of conventional security systems in detecting new or anomalous network attacks. Traditional systems generally rely on predefined attack signatures, making them ineffective against previously unknown attacks. Therefore, this study proposes a solution by implementing the Support Vector Machine (SVM) method for automatic network attack detection. The research method includes the collection of campus network traffic data, data preprocessing stages such as data cleaning, normalization, and feature selection, SVM model training, and performance evaluation using confusion matrix and ROC curve. The results show that the SVM model is able to classify normal traffic and attack traffic with very high accuracy. These findings indicate that SVM is an effective method for intrusion detection and can significantly enhance campus network security in an adaptive and efficient manner.